#DoNotTouchMyClothes: The protest of afghan women on social media against the Taliban (Research, Society and Development, 2025)
This study aims to analyze the discourses produced by Afghan women within a socially situated context shared with the researchers. It seeks to understand who these women are based on the construction and circulation of their statements on social media, as well as to discuss the role of clothing as a form of political protest in their publications. In this sense, we aim to understand the socio-historical context of the discourses produced by Afghan women through the sharing of the hashtags #DoNotTouchMyClothes and #AfghanistanCulture, and the formation of these discourses within the digital environment, emphasizing the use of clothing as a form of resistance and political protest. The analysis is guided by authors such as Cristiane Dias (2018), Eni P. Orlandi (2005, 2006, 2015), and Aline Bocchi (2017), among others, who help develop the analytical perception of the texts under our observation. During the course of this study, we recognized the need to reflect on who holds the power of speech within the discourses analyzed here. The texts in question were produced by Afghan women who no longer live in Afghanistan. We also highlight the universalization of a discourse that originates from the individual experience, seeking to generate identification.